Iktisāb al-Lugah al-‘Arabiyyah min al-Bī`ah al-Iṣṭinā’iyyah bi Jāmi’ah Maulānā Mālik Ibrāhῑm Malang - Uril Bahruddin; Syuhadak Syuhadak; Sutaman Sutaman (LISANIA: Journal of Arabic Education and Literature, 2021)
Language environment has been used as an Arabic learning strategy. However, not every strategy is successful in improving Arabic language competence. This article aimed at understanding: (1) the phenomenon of the establishment of Arabic language environment in higher education, and (2) the contribution of Arabic language environment in improving language competence through the language acquisition process. So far, these aspects were neglected in previous studies. This research used a qualitative approach with a case study model. Data were collected through interviews, observation and documentation. They were analyzed in detail since the beginning of collection, description and reduction, and verification. The results showed that the establishment of language environment at UIN Maulana Malik Ibrahim Malang was carried out by establishing student dormitories, native speakers and student activity forums such as Arabic camp, public lectures, debates, discussions, public speaking, learning outside the classroom and competition. The influence of the Arabic language environment on the language acquisition is indicated by the students' speaking ability after 6 months of learning Arabic, participation in Arabic competition, writing Arabic scientific papers, and using Arabic in learning meetings. In conclusion, it turns out that the establishment of an Arabic language environment can be carried out in universities and can improve Arabic language competence. This article provided suggestions for effective use of the Arabic language environment as a language skill learning strategy.